«POETIC CONCEPTION WITH MUSICAL AND PAINTER BACKGROUND» OF MYHAYLO YATSKIV IN THE NEWEST STUDY INTERPRETATION OF LITERATURE Melnyk O. Modernistic phenomenon of Myhaylo Yatskiv: canon and interpretation / Oksana Melnyk; National academy of sciences of Ukra - Mochernyuk , N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses the book of young author from Lvov of Oksana Melnyk about the modernistic phenomenon of artistic world of Myhaylo Yatskiv.